Investigating the Effect of Heat Transfer Driving Force and Seed Loading on the Batch Eutectic Freeze Crystallization of a Dilute Brine - Spencer, Anotidaishe (Department of Chemical Engineering, 2024)
Eutectic Freeze Crystallization (EFC) is a separation technology that separates solute from solvent. It is often used as a wastewater treatment process for industrial brines. In EFC, the solution is cooled to temperatures below the eutectic point of the brine, such that ice and salt simultaneously crystallize out of solution. Solid-solid-liquid separation of the resulting suspension is achieved by exploiting differences in the densities of the phases. EFC has been found to perform well when applied to concentrated brines, but not with dilute brines. Previous studies have shown that the chosen operating conditions for the crystallizer can result in phenomena that limit achievable yields and product purities. These phenomena are more severe when dilute brines are treated. One of these limiting phenomena is heat transfer, which is the principle that makes EFC possible. Understanding how operating conditions are related to the production of ice and salt through heat transfer can lead to better control of the EFC process. This would allow for consistent production of ice and salt at high yields and product purities, even for dilute brines. The heat transfer driving force (ΔTLMTD) and ice seed loading (SL) are two operating conditions that are of interest in this work as they are linked to heat transfer; ΔTLMTD, directly by affecting the heat transfer rate and in turn the production capacity of a crystallizing system, and SL indirectly by forming the initial magma density (solid content in the crystallizer by mass) which affects crystallization location and the hydrodynamics of the system. These two operating conditions were chosen because their effect on production of ice and salt from dilute brines has not been studied before. The aim of this work was to understand how SL and ΔTLMTD affect the yield of ice and salt and the purity of ice, in batch EFC. A synthetic Na2SO4 solution was used for crystallization experiments as its eutectic composition is dilute (4wt.%). Ice seed loadings between 0 and 12 wt.% and ΔTLMTD values between 2 and 10℃ were investigated. The yields of ice and salt, as well as the purity of ice, were measured to determine the relationship between ΔTLMTD and the yield of ice and salt, ΔTLMTD and ice purity, SL and the yield of ice and salt, and SL and ice purity. It was found that as the ΔTLMTD increased, the yield of ice and salt increased, due to the higher heat transfer rate. The ice yield was a sum of ice harvested from the bulk and ice formed on the wall (scale). The yield of ice in the bulk decreased with increasing ΔTLMTD, whilst the yield of scale increased. As ΔTLMTD increased, the cooled wall became colder, therefore the fluid closest to the wall had the most supersaturation. This led to the formation of a scale layer. The combination of increased driving force and shortened scale formation time resulted in the observed increase in the scale yield. This increase in the scale yield increased heat transfer resistance between the coolant and the bulk, which produced less ice in the bulk. It was also found that the purity of ice decreased as ΔTLMTD increased. The salt particles were much finer than the ice particles (ice was >13 times larger than salt). The large difference between the ice and salt crystals, combined with increased salt production and intense mixing resulted in an increase in salt entrainment. Increased salt entrainment resulted in poor separation, and a reduction in ice purity was observed. It was found that increasing the ice seed loading increased the yield of ice in the bulk and decreased the scale yield. A maximum in ice in the bulk and a minimum in the scale resulted from a seed loading of 9 wt.%. Solids in the system provided sufficient surface area to promote secondary nucleation and growth in the bulk such that heterogeneous nucleation at the wall was minimised. This reduced the propensity for scale formation. Once the seed loading increased to 12 wt.%, the mixing efficiency of the system decreased. This resulted in localised supersaturation at the wall, which in turn resulted in a scale layer. The reduced mixing efficiency increased the resistance to heat transfer within the bulk, resulting in reduced crystallization within the bulk, therefore the yield of ice in the bulk decreased. It was also found that the salt yield decreased as the seed loading increased. This was due to poor separation caused by the increase in magma density and increase in salt entrainment. The entrained salt in the ice product was washed off rather than harvested, explaining the low salt yield obtained. The salt product was small (80µm <mode< 120µm), and the wash water was increased as seed loading increased. This made washing more efficient and produced a purer final ice product.